Validity of the TBApp mobile application for self-care management for people with tuberculosis - Lara Bezerra de Oliveira de Assis; Denise Maria Guerreiro Vieira da Silva; Jucimar Maia da Silva Junior; Edinilza Ribeiro dos Santos; Jair dos Santos Pinheiro; Daniel Souza Sacramento; Hermann Jacques Hernani de Oliveira; Amélia Nunes Sicsú (Associação Brasileira de Enfermagem, 2024)
ABSTRACT Objectives: to describe the validity process of the TBApp mobile application for self-care management for people with tuberculosis linked to Primary Health Care. Methods: methodological research developed with ten expert judges, carried out virtually. The application was assessed in relation to content and technology quality in seven domains (objectivity; structure and appearance; relevance; functionality; reliability; usability; and efficiency), using an instrument with a Likert scale. Results: TBApp was considered valid, relevant, functional, reliable and effective by expert judges. The objectives, structure and presentation and relevance domains presented an overall Content Validity Index of 0.93, and the functionality, reliability, usability and efficiency domains presented characteristics and sub-characteristics values greater than 0.80. Conclusions: TBApp is a creative and innovative tool that can be used by people with TB and disseminated in the scientific community.